Interactive shape modelling in unity 3D system - Yan, Wei (Nanyang Technological University, 2024)
Computer graphics is the creation and representation of images using computers. This involves the study of geometry and colours through mathematical formulas, as well as time-dependent models used for implementing animations. ShapeExplorer is a custom-made software developed for the study of computer graphics that can generate two or three-dimensional shape visualisations based on user-defined parameters and functions. It includes support for implicit and parametric formulas, among a plethora of other features. Recently, virtual and augmented reality (VR/AR) applications have seen greater use and effectiveness as educational tools. VR/AR products have also become viable for commercial use. One such product is the Leap Motion Controller (LMC) from Ultraleap, a hand tracking camera that can accurately calculate a person’s hand position and orientation in real time. This study aims to introduce hand tracking capabilities to ShapeExplorer by integrating it with the Unity game engine. With hand tracking, quick manipulations (translation/scaling/rotation) of multiple objects within the same scene are made possible in ShapeExplorer, greatly improving the user experience of the software.